RANCANG BANGUN SISTEM IT HELPDESK BERBASIS WEB PADA YAYASAN XYZ JAKARTA - Setiawan; Teddy Setiady; Hanif Deriansyah (POLITEKNIK LP3I JAKARTA, 2024)
An IT Helpdesk system is a system designed to help an organization or company that aims to handle technician support requests from users. This system also aims to speed up and make it easier to solve a problem as well as increase the efficiency of support from technicians, reduce problem resolution time, and increase user satisfaction. But this is not the case with Yayasan Adikara Intention Regina Pacis Jakarta, where in overcoming a problem in submitting damage or repairs made by users to the IT (information and technology) team has not been able to work efficiently, resulting in dissatisfaction from users